IMPEACHMENT DALAM UUD 1945 PASCA AMANDEMEN - Rahman, Abdul (DIKTUM: Jurnal Syariah dan Hukum, 2016)
Impeachment of the president and / or vice president from office is not new in the constitutional system of Indonesia. Before the amendment, Indonesia also has a mechanism of impeachment that the President and / or Vice President may be removed from office, as had happened during the Sukarno and Abdurrahman Wahid. However, the impeachment process through a political process and a new law set in the 1945 amendment after amendment. The reasons for the impeachment of a limited manner specified in the constitution, although the reasons have a very wide interpretation and may be subjective, especially in a political institution in the House. There are several things that must be done to complete the impeachment mechanism rules in Indonesia, among others: (a) relating to the impeachment process in the House of Representatives; and (b) the impeachment proceedings in the Constitution Court.